EFEKTIVITAS PENERAPAN PEER TEACHING DALAM MENINGKATKAN TAHSIN AL-QUR’AN DI MADRASAH TSANAWIYAH : (STUDI KOMPARASI DI MTS. AL-IKHLAS JAWILAN DAN MTS. AL-AMIN KOPO KABUPATEN SERANG) - Amin Noval, Muhamad (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
The purpose of this study was to determine: (1) to determine the application of peer teaching in improving the tahsin of the Qur'an at MTs Ikhlas Jawilan; (2) to find out the application of peer teaching in improving the tahsin of the Qur'an at MTs Al-Amin Kopo; (3) to find out the comparison of the effectiveness of the application of peer teaching in improving the tahsin of the Qur'an; (4) to find out the factors that support and inhibit the application of peer teaching in improving the tahsin of the Qur'an at MTs Ikhlas Jawilan and MTs Al-Amin Kopo Serang. The research method uses mixed methods (mixed methods) with the type of experimental research. Combining two forms of research that have existed before, namely quantitative research and qualitative research. The research was carried out at MTs Ikhlas Jawilan and MTs Al-Amin Kopo Serang. Data analysis techniques include combined methods (Mixed Methods Research), namely: (1) qualitative data analysis; interviews, observations, and documentation. (2) quantitative data analysis; describe the effectiveness of learning includes student learning outcomes. The results showed that; (1) the implementation of peer teaching at MTs Ikhlas Jawilan conducted by the Al-Qur'an Hadith teacher went well. Teachers supervise, organize groups, adjust schedules, overcome difficulties, improve competency achievement, manage teacher administration, and evaluate every month. (2) the application of peer teaching at MTs Al-Amin Kopo, divided into three stages; planning, implementation and evaluation. (3) a comparison of the effectiveness of the application of peer teaching in improving the tahsin of the Qur'an in the two MTs, through: (a) the planning stage; has a syllabus as a teacher's guide which is described as a lesson plan. (b) implementation stage; the interaction of various components of teaching, including; Teachers, Content or learning materials, and Students. The steps consist of; introduction, core activity, closing activity. (c) evaluation stage, there are two stages; (a) formative evaluation at the end of the learning unit. (b) summative evaluation, a certain period of time. (4) Supporting factors; (a) can improve tahsin Al-Qur'an well, (b) build interaction in class; between teachers and students, students and students, (c) students' interest in learning is quite high, especially in tahsin Al-Qur'an, (d) there is intensive and intimate communication between teachers and students in the learning process, and (e) an atmosphere of class is more interesting and active. While the inhibiting factor; (a) the lack of tutor preparation, due to limited time, (b) inadequate classroom infrastructure, (c) less conducive learning activities, the number of students exceeds the standard (MTs. Al-Ikhlas Jawilan), so its implementation is difficult to control, (d) less learning resources. (5). The results of studying Al-Qur'an Tahsin at MTs Ikhlas Jawilan and MTs Al-Amin Kopo Serang Regency have changed because there are students who cannot recite the Al-Qur'an and then these students can do Tahsin Al-Qur'an. Teachers at MTs Ikhlas Jawilan and MTs Al-Amin Kopo, Serang Regency have also evaluated the results of learning Al-Qur'an Tahsin with instruments that are in accordance with the indicators and learning objectives of Al-Qur'an Tahsin learning. (6). There is no significant effect of peer teaching in improving Al-Qur'an Tahsin at MTs Ikhlas Jawilan and MTs Al-Amin Kopo, Serang Regency.